2017
DOI: 10.1080/02656736.2017.1284349
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of an MR-compatible microwave ablation system and comparison with a standard microwave ablation system in an ex vivo bovine liver model

Abstract: The tested MR-compatible system can be used without loss of ablation performance compared to the standard system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In our study, the SI ranged from 0.68 to 0.75. This value is similar to those reported for high-power MWA systems for conventional guidance techniques and higher than the SI value for a non-perfusion cooled MR-conditional system which has been reported to range from 0.36 to 0.59 [31].…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the SI ranged from 0.68 to 0.75. This value is similar to those reported for high-power MWA systems for conventional guidance techniques and higher than the SI value for a non-perfusion cooled MR-conditional system which has been reported to range from 0.36 to 0.59 [31].…”
Section: Discussionsupporting
confidence: 86%
“…The formation of air bubbles during ultrasound-guided ablation results in a blurred boundary. Thus, MR-guided ablation plays a very important role in the ablation of very small lesions and lesions at specific locations 26 , 27 . It has been reported that poor display of the microwave applicator tip (length, 1.6 cm) on T1WI may be related to the ceramic structure of the tip, especially for oblique noncoplanar puncture, but the depth and shape of the applicator tip can be observed better after scanning along the long axis of the microwave applicator 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrating microwave ablation systems with MRI may be challenging due to the need to design the ablation applicators and feeding cables from MRI-conditional materials, as well as considerable attenuation in long feeding cables due to the requirement that the microwave power source is placed outside the scanner room. 31 Some prior studies have investigated the use of 1.5 T MRI thermometry for monitoring microwave heating of ex vivo tissues such as brain, muscle, liver, kidney, in vivo rabbit brain, as well as ablation of prostate cancer in humans. [32][33][34] In these studies, MR thermometry images were acquired with different imaging sequences such as spoiled gradient-recalled echo (SPGR) and fast-SPGR in a single plane with an update time of~13-26 s. Prior studies have also employed gradient eco sequences (GRE) with Z-shimming for minimizing artifacts in the proximity of metallic microwave ablation applicator.…”
Section: Introductionmentioning
confidence: 99%
“…While MR thermometry has been widely applied for monitoring and guiding delivery of ultrasound and laser ablation, 26–30 it has not been widely used with microwave ablation systems. Integrating microwave ablation systems with MRI may be challenging due to the need to design the ablation applicators and feeding cables from MRI‐conditional materials, as well as considerable attenuation in long feeding cables due to the requirement that the microwave power source is placed outside the scanner room 31 . Some prior studies have investigated the use of 1.5 T MRI thermometry for monitoring microwave heating of ex vivo tissues such as brain, muscle, liver, kidney, in vivo rabbit brain, as well as ablation of prostate cancer in humans 32–34 .…”
Section: Introductionmentioning
confidence: 99%